Interest rate pass-through in Turkey and impact of global financial crisis: asymmetric threshold cointegration analysis - Yüksel, Ebru; Özcan, Kıvılcım Metin (Journal of Business Economics and Management, 2013)
This paper aims to investigate the interest rate pass-through of monetary policy rate to banking retail rates in Turkey by employing the asymmetric threshold autoregressive (TAR) and momentum threshold autoegressive (MTAR) procedures introduced by Enders and Siklos (2001). Over the period December 2001 to April 2011, the empirical results of asymmetric threshold cointegration analysis suggest that there exist significant and complete pass-through between policy rate and loan rates. Positive and negative departures from the equilibrium converge to long run path almost at the same speed. Pace of convergence is about two to three months for all loan rates. Policy rate has significant short run impact on loan rates. Our analysis revealed that there is no significant relationship between policy rate and bank deposit rates due to sluggish adjustment of deposit rates. Lastly, the speed and behavior of interest rate pass-through between policy rate and loan rates did not change when we encounter the effect of 2008 financial crisis. Having a banking sector dominated financial system in Turkey, the results suggest that banks adjust loan rates faster than deposit rates. This indicates that Central Bank can affect the consumption behavior of people, in other words aggregate demand through loan rates.First published online: 12 Sep 2012